Aspects of the legal provision of competitiveness in the electoral process of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article is devoted to the problems of legal support of objective political competition during the electoral process in the Republic of Kazakhstan. The purpose of the work is to analyze the problems of the functioning of Kazakhstan’s electoral legislation and political competitiveness in the context of the study of certain principles of electoral law. In particular, the issues of practical implementation of alternativeness and competitiveness as mandatory attributes of the modern democratic electoral process. The urgency of the problem is determined by the socio-political significance for the Kazakhstani state and the society of the institution of fair elections as a component of their democratic development. When writing the article, both general scientific and private scientific methods of research (dialectical, historical, comparative legal, special-legal, logical) were used.The practical significance of the article lies in the possibility of using the results obtained in improving the existing electoral legislation of the Republic of Kazakhstan, as well as in law enforcement practice in the sphere of elections of various levels.Key words: alternative elections, competitiveness, competition, electoral process, voting, electoral legislation, election campaign, electoral rights, principles.